Dinamika Kajian Pendidikan Bahasa Arab Dalam Sripsi Mahasiswa Program Studi Pendidikan Bahasa Arab Antara Tahun 2010-2014 Fakultas Ilmu Tarbiyah Dan Keguruan IAIN Surakarta - Ghofur, Abdul (ARABIYATUNA : Jurnal Bahasa Arab, 2017)
This research departs from academic anxiety, the thesis is only used as an annual ritual for the graduation requirements of students, regardless of competence standards, methodological, and actuality issues about education, especially ignored Arabic. In this case thesis student of Arabic Education Study Program (PBA) IAIN Surakarta year 201-2015. The few questions that will be answered in this study are: what are the Arabic educational clusters that have been studied; What percentage, which clusters are already saturated and need to be abandoned to avoid repetition; What clusters are still open opportunities to serve as a topic of study in the future; How its adaptability to the new educational issues being in the community, and what are the methodological problems that are often found. This study includes literary because the data and primary sources are derived from written materials derived from the thesis of students Prodi PBA FITK IAIN Surakarta 2010-2014. This research is descriptive qualitative, data collection using documentation technique. The written data collected and categorized and then analyzed inductively by content analysis method (content analysis). Data analysis technique is an interactive analysis model, namely: data reduction data, and drawing conclusions. The result of this research shows that from 98 thesis amount, "Typology of Study" data of Thesis student of PBA FITK IAIN Surakarta 2010-2014, a normative study is 72 (73.47%), and the sociology of education is 16 (16.33%). For the actuality of the issue, students of PBA FITK are about the problem of applying methods and approaches in learning Arabic. While issues related to current issues concerning the education of Arabic language, such as translation, content analysis, and character thinking, have not been raised much. While methodologically, the most errors that are found from the students thesis Prodi PBA is in aspects of the theoretical framework, data analysis, and other grammar.